BASIC TRAINING OF TOURISM HUMAN RESOURCES FOR THE SITU GEDE VILLAGE COMMUNITY, BOGOR: EFFORTS TO INCREASE LOCAL CAPACITY AND DEVELOP ECOTOURISM - Rainanto, Bambang Hengky; Suryanti, Cecilia Valentina Srihadi; Saragi, Charles Parnauli; Yuwantiningrum, Sri Endah; Manurung, Tarida Marlin Surya; Utami, Nisa Rahmaniyah; Nurachmad, Edi; Hermawan, Yanto (LPPM Univ. Ibn Khaldun Bogor, 2025)
This training program aims to improve the capacity of local human resources in managing the ecotourism potential of Situ Gede, Bogor. The activity was held on August 10, 2023 at the Rizen Padjadjaran Hotel, Jl. Binamarga II, Baranangsiang, Bogor City. The core focus of this training is to provide basic knowledge about the concept of tourism, quality visitor services, environmental management, and community-based marketing strategies. A total of 30 participants consisting of local residents, tourism managers, and small and medium enterprises (SMEs) of Situ Gede Village participated in the activity. The implementation method consisted of interactive lectures, field-based practices, and group discussions. The results of the training showed a significant increase in participants' understanding of the structure of tourism management, the importance of providing friendly and professional services, and the basic principles of environmental conservation. In addition, participants began to realize the importance of utilizing social media platforms as an effective promotional tool to attract visitors. The results of the pre-test and post-test evaluations showed an average increase in knowledge of around 60%. This activity shows a positive impact as an initial step in developing competent tourism human resources. Based on these findings, it is recommended that further training be conducted with an emphasis on developing thematic tour packages, increasing capacity in digital marketing, and establishing strategic collaborations between tourism stakeholders and local small businesses.